Hydraulic Optimization of Two-Way Counter-rotating Axial Flow Pump Turbine - Xiuli, Wang; Bin, Lin; Yang, Li; Yan, Zhang; Rongsheng, Zhu; Yun, Long; Qiang, Fu (Frontiers in Energy Research, 2020)
The two-way counter-rotation technology is mainly applied to the tidal power station. In this paper, the hydrodynamic optimization of the two-way counter-rotating axial-flow pump turbine is carried out. Under the premise of realizing the forward and reverse power generation and the forward and negative pumping basic function, it has important engineering significance and academic value for improving the pump turbine performance of various working conditions. The main contents are as follows: hydraulic design of “S”-shaped blade for the two-way counter-rotating axial-flow pump turbine is conducted, and the influence of the gap between different impeller stages on the performance is calculated and analyzed, and the variation law of head and efficiency of the pump turbine under different inter-stage clearances is obtained. And the influence of the inter-stage gap on the unit is summarized from the vorticity distribution and the axial section pressure cloud diagram analysis, and the range of the best inter-stage gap of the unit performance is determined.